UPAYA GURU TAHFIDZ AL-QUR’AN DALAM MEMBENTUK KEPRIBADIAN QUR’ANI PADA SISWA SMP AL-QUR’AN PONDOK PESANTREN TRI BHAKTI AT-TAQWA LAMPUNG TIMUR [THE EFFORT OF TEACHER TAHFIDZ AL-QUR’AN IN FORMING THE QUR'ANI PERSONALITY IN STUDENTS OF SMP AL-QUR’AN PONDOK PESANTREN TRI BHAKTI AT-TAQWA LAMPUNG TIMUR] - Suwardi, S; Jannah, Siti Roudhotul; Syaifullah, Muhammad (Acta Islamica Counsenesia: Counselling Research and Applications, 2022)
This study aims to describe the efforts of Tahfidz Al-Qur'an teachers in shaping the Qur'anic personality for students of SMP Al-Qur’an Pondok Pesantren Tri Bhakti At-Taqwa Lampung Timur. The research method uses a qualitative study with a case study approach. The data collection techniques used in this study were observation, interviews, and documentation. The results obtained are to form a Qur'anic personality which consists of a repentant soul formed by a teacher acting as a corrector, to form a pious spirit, a teacher acts as a motivator, to form an ihsan soul, a teacher acts as a facilitator, and to form a spirit of ihsan, a teacher acts as an motivator, and to form a positive spirit then a teacher acts as an organizer.